PENGARUH OWNERSHIP STRUCTURE TERHADAP FIRM VALUE DENGAN VOLUNTARY DISCLOSURE IN CORPORATE GOVERNANCE SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN TAHUN 2011-2016) - Susanna Susanna Susanna; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aimed to examine the influence of ownership structure on firm value through voluntary disclosure in corporate governance as mediating variable. This study also examined the indirect influence of ownership structure on firm value through voluntary disclosure in corporate governance as mediating variable. The data were obtained from 39 mining sector companies listed in Indonesia Stock Exchange from 2011-2016 and data were collected from annual reports and financial reports and processed by using WarpPLS software version 5.0.This study used a quantitative approach where the data obtained from company’s financial statement of 2011-2016. The data then processed by using PLS software. The result showed that there was positive and significant influence of ownership structure toward firm value, negative and significant influence of ownership structure toward voluntary disclosure in corporate governance, and negative and significant influence of voluntary disclosure in corporate governance toward firm value. The voluntary disclosure in corporate governance was successful in mediating the indirect influence of ownership structure and firm value